SANTUNAN OLEH PELAKU TINDAK PIDANA TERHADAP KORBAN KEJAHATAN DIKAJI DARI KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (KUHAP) - Bayu Ardana, Ida Bagus; Subha Karma Resen, Made Gede (Kertha Wicara : Journal Ilmu Hukum, 2014)
This paper entitled "Compensation By Performers Crime Against Crime Victims Studied From the Code of Criminal Procedure." This paper using the methods of normative research for this paper examined by the Criminal Procedure Code which has not been set on the compensation by the perpetrator. Article discusses the practice of granting compensation by the perpetrator of the crime victim. known as Indonesian criminal Procedure Code only stipulates the compensation and not explaining the provision of compensation to victims of crime. vacancy this then raises the norm so it is necessary the existence of a clear recognition of the provision of compensation to victims of crime
Keywords: Compensation, Criminal Offender, Victims of Crime